PENGARUH PENCAMPURAN BROWN GAS KE BENSIN PREMIUM UNTUK MOTOR BENSIN YANG DIPASANG PADA SEPEDA MOTOR SUZUKI SMASH 110 CC - Desly Theo Daud Bawiling; Hardi Gunawan; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
This research is aimed to determine the effects of brown gas mixed with gasoline on fuel consumption of a Suzuki Smash 110cc. Data taken in this study is the fuel consumption of the vehicle on different gear ratio, and velocity of the vehicle within a distance of 2.5 km. Analyzing is done on gear ratio-1 at 10,15,20,25,30 km/h, whereas on gear ratio-2,3 and 4 at 20, 25, 30, 35 and 40. The result of observations and computation shows fuel consume rate gear ratio-1 is 266,4; 349,3; 455,1; 562,6 and 697,5 gr/hr on gear ratio-2 is 359,2, 410,9, 439,0; 545,9 and 648,9 gr/hr, on gear ratio-3 is 296,9; 295,8; 408,6; 494,4 and 624,5 gr/hr, on gear ratio-4 is 201,9; 249,4; 412,0; 330,8 and 538,0 gr/hr with the speed of 20, 25, 30, 35 and 40 km/h consecutively. The conclusion is the higher the speed of motorcycle, the greater the rate of consumption. It was found that the testing is executed in the range of engine speed of 2136 to 6182 rpm. These results demonstrate that the motor cycle is more efficient if using gears ratio-4 at a speed of 20 km/h to 40 km/h. Key Word : fuel consumption , brown gas, gasoline engine, Suzuki Smash 110cc.